An investigation into the realization of children’s rights in South Africa : perceptions of Afrikaans-speaking primary caregivers of children with intellectual disabilities - Bornman, Juan, 1968- (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2012.